Decomposition Technique and a Family of Efficient Schemes for Nonlinear Equations - Farooq Ahmed Shah; Maslina Darus; Imran Faisal; Muhammad Arsalan Shafiq (Discrete Dynamics in Nature and Society)
Various problems of pure and applied sciences can be studied in the unified framework of nonlinear equations. In this paper, a new family of iterative methods for solving nonlinear equations is developed by using a new decomposition technique. The convergence of the new methods is proven. For the implementation and performance of the new methods, some examples are solved and the results are compared with some existing methods.